Utility of the Rey 15-Item Test for detecting memory malingering - Janavičiūtė, Jovita; Lelytė, Inesa; Žukevičius, Algirdas; Vilcinis, Rimantas; Pranckevičienė, Aistė (Psichologija, 2021)
People seeking higher privileges or disability benefits are prone to simulate cognitive difficulties (van Oorsouw, Merckelbach, 2010). The most common is the simulation of memory impairment, but there is no adapted test in Lithuania that could identify it. The purpose of this study is to determine Rey Fifteen-Item Test (FIT; Rey, 1964; Lezak, Howieson, Bigler, Tranel, 2012) sensitivity and specificity by comparing three groups of subjects: healthy responders, who perform tests, as usual, healthy responders, who were instructed to simulate memory impairments and patients with traumatic brain injuries. The study included 91 subjects aged 18 to 86 years (M=42.04 SD=13.5). The study used the “Short Term Memory Test” (STMT; Vasserman, Dorofeeva, Meyerson, 1997), the FIT, socio-demographic questions. The results of the study revealed that the malingerers and nonmalingerers did not differ in the STMA scores. Whereas in patients with traumatic brain injuries STMA scores were significantly lower. Nonmalingerers and patients with traumatic brain injuries performed better on FIT than malingerers. The probability that the malingerers score lower than people with memory difficulties is 62 up to 78 percent; FIT sensitivity ranges between 73 and 90 percent, specificity between 41 and 72 percent, depending on the RPOT cut-off score.